The Influence Of Tourist Visits On The Welfare Of The Surrounding Community (Case Study Of Selemak Deli Serdang Village) - Lubis, Mutiara; Jannah, Nurul; Dharma, Budi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2017)
The purpose of this study is to determine the impact of village welfare on tourists' visits to Selemak Village in Deli Serdang. In this study, wellbeing is the dependent variable and tourist visits are the independent variable. A quantitative technique including causality investigations is employed. Saturated sampling was used in this study to choose 50 village vendors as samples. There will be fifty respondents in all that the researchers employ for this study. Data were collected using a Likert scale questionnaire, and the SPSS version 26 program was utilized for basic regression analysis. With a regression coefficient of 0.443, the research demonstrates a positive association between tourist visits and community wellbeing. This implies that a 1% increase in tourist visits might result in a 0.443% improvement in community welfare. The tourist visit variable explains 17.8% of the variability in community wellbeing, with other factors influencing the remaining portion, according to the coefficient of determination (R2). The wellbeing of the community in Selemak Village, Deli Serdang, is significantly impacted by tourist visits, according to the study's findings. Tourism managers and regulators may utilize research findings as a starting point to develop strategies and rules that more effectively increase visitor visitation.